A Case of AIDS Diagnosed in the Intensive Care Unit with Concurrent Influenza Infection and Pneumocystis jirovecii Pneumonia - Yeliz Özdemir; İlhan Bahar; Gülfem Ece (Case Reports in Medicine)
Conclusions: Community-acquired pneumonia is common in PLWH, especially among those not receiving antiretroviral therapies (ART). Co-infections with bacterial, viral, and fungal pathogens are common. Early identification of etiological agents and prompt treatment are crucial for improving patient outcomes.